Vai trò trung gian của khai thác kiến thức số trong nâng cao lợi thế cạnh tranh bền vững: Trường hợp của các doanh nghiệp sản xuất vừa và nhỏ Việt Nam - Đinh Văn, Hoàng; Dương Bích, v; Vũ Hồng, Hà; Lê Hiền, Trang; Nguyễn Ngọc Ngân, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2025)
The study examines the mediating role of digital knowledge exploitation between digital capabilities and sustainable competitive advantage while assessing digital leadership’s impact on Vietnamese small and medium-sized manufacturing enterprises (SMEs). Using a quantitative method with partial least squares structural equation modeling (PLS-SEM) to analyze 398 responses, the study shows digital capabilities positively influence digital knowledge exploitation, which in turn enhances sustainable competitive advantage. Digital leadership positively affects digital knowledge exploitation but does not directly impact digital capabilities and sustainable competitive advantage. Based on these findings, managerial implications are proposed to enhance sustainable competitive advantages for Vietnamese manufacturing SMEs through advancing digital capabilities and knowledge exploitation, emphasizing digital leadership’s supporting role.